Pathways to Development Empowering Local Women to Build a More Equitable Future in Vietnam - Tran, Phuong Thi Minh (World Bank, Washington, DC, 2012)
Vietnam's economic emergence is perhaps best experienced along its rural roads: over 175,000 kilometers of pavement, rubble, and dirt track extend to two-thirds of the country's population, including nearly all of the poorest people, who live among its productive farms, lush forests, and meandering river valleys. In recent years, road investments in Vietnam's rural areas have improved socioeconomic development and have promoted gender equity, social participation, improved school attendance, and more inclusive health services to impoverished regions. However, all but a few hundred communes remain off-grid, and infrastructural roadblocks and bureaucratic potholes have delayed the goal of a fully integrated road system. The World Bank's Third Rural Transport Project (RTP3) supported a win-win solution: employing ethnic minority women to sustainably manage road maintenance through an innovative participatory approach to local development. This smart lesson describes the experience of improving the roads and women's lives in rural Vietnam.